The Presence of Holiness in Landscape and the Ecstasy of Colours in Lithuanian Poetry of the Second Half of the Twentieth-Century: The Footprint of Mikalojus Konstantinas Čiurlionis - Bernotienė, Gintarė (Colloquia, 2025)
The article discusses the reception of some ideas and worldview adopted from Mikalojus Konstantinas Čiurlionis’s paintings by poets Sigitas Geda, Leonardas Gutauskas and Jonas Juškaitis, who debuted in the 1960s and were sensitive to the mysticism of nature. Radosław Okulicz-Kozaryn’s arguments that the Polish literature, especially Juliusz Słowacki’s poems (the historiosophical poem “Anhelli” and the epic-symbolic poem “The Spirit King,” describing the history of the Polish nation as a series of incarnations of the national spirit) had an influence on Čiurlionis’s art encouraged to look deeper into metaphysical thinking and experiences of holiness discussed more widely in Lithuanian academic texts in the twenty-first century. Evident in the Čiurlionis’s work, they have been manifested in Lithuanian poetry through ecstatic visions of colour, high style rhetoric and hermetic imagery. The comparative method enabled to highlight the overlaps in the perception of Čiurlionis and the aforementioned poets in art and poetry, noting the close relationship between landscape and historical themes. The author of the article considers the influence of Čiurlionis’s apolitical work on the theurgic ethos of poetry and the pathos of the cultural of resistance during the Soviet era, as well as the formation of the image of Čiurlionis as a national genius in poetry after 1990.
Keywords: Mikalojus Konstantinas Čiurlionis; Juliusz Słowacki; Sigitas Geda; Leonardas Gutauskas; Jonas Juškaitis; metaphysics; historiosophy